2022
DOI: 10.1111/jdv.18063
|View full text |Cite
|
Sign up to set email alerts
|

Erythema multiforme in COVID‐19 patients and following COVID‐19 vaccination: manifestations, associations and outcomes

Abstract: inpatients for 17 months the prevalence of 0.56% is thought to accurately reflect the clinical situation.We also reveal that maculopapular lesions are common (75.0%) in Japan. The most common COVID-19-related skin rash was reported to be pseudo-chilblain lesions (40.9%) and 97% of these cases were from Europe or the USA. 4 The differences in cutaneous patterns may owe to a genetic/racial predisposition. The minor allele frequency of the IFIH1 gene which is common in Caucasians increases the production of type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…140 This led to the hypothesis that the crusts suffered by the patients potentially are actually not an oral manifestation of SARS-CoV-2, but probably erythema multiforme, which is the distinct pathognomonic features that also include hemorrhagic crusts along with targetoid lesions on the skin. 138,142 Our findings highlighted that most of the skin lesion-related medications were exanthema and skin or genital ulceration 5, 12 and 16). In contrast, some cases also reported similar skin lesions in the patient without any medication (Tables 6, 10 and 14).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…140 This led to the hypothesis that the crusts suffered by the patients potentially are actually not an oral manifestation of SARS-CoV-2, but probably erythema multiforme, which is the distinct pathognomonic features that also include hemorrhagic crusts along with targetoid lesions on the skin. 138,142 Our findings highlighted that most of the skin lesion-related medications were exanthema and skin or genital ulceration 5, 12 and 16). In contrast, some cases also reported similar skin lesions in the patient without any medication (Tables 6, 10 and 14).…”
Section: Discussionmentioning
confidence: 70%
“…138 Hydroxychloroquine has been used to treat COVID-19 and was reported to be one of the most prevalent erythema multiforme-triggering drugs and various other side effects in patients. [138][139][140][141][142] The lesion was caused by promoted CD8+ lymphocyte infiltration to the epithelial tissue, thus leading to the necrosis of the cells and subepithelial cleft forming as a hypersensitivity reaction to the drugs consumed. 140 This led to the hypothesis that the crusts suffered by the patients potentially are actually not an oral manifestation of SARS-CoV-2, but probably erythema multiforme, which is the distinct pathognomonic features that also include hemorrhagic crusts along with targetoid lesions on the skin.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this combination of drugs could have caused a hypersensitivity reaction due to an increase in serum levels of any of these drugs. It is also possible that the rash is secondary to the COVID-19 infection itself, as prior studies have suggested that EM may form weeks after the start of the COVID-19 infection [ 18 ]. Similarly, this patient’s EM reaction occurred after the completion of Paxlovid™ and after the first admission.…”
Section: Discussionmentioning
confidence: 99%
“…EM due to COVID-19 vaccination occurred most often after the first dose, most commonly with mRNA vaccines in one study ( 15 ). In another study, EM was more commonly reported in COVID-19 infection compared to COVID-19 immunisation ( 16 ). Small numbers of cases make it challenging to establish a causal relationship.…”
Section: Erythema Multiformementioning
confidence: 99%